2021
DOI: 10.1016/j.scr.2021.102560
|View full text |Cite
|
Sign up to set email alerts
|

Increasing cytosolic Ca2+ levels restore cell proliferation and stem cell potency in aged MSCs

Abstract: Aging is an inescapable complex physiological but extendable process, and all cells, including stem cells, are altered over time. Diverse mechanism(s) could modulate stem cell number, their proliferation rate, and promote tissue repair during aging that leads to longevity. However, the factors that could restore aging stem cell potency and would lead to healthy aging are not fully identified. Here we show that maintaining cytosolic Ca 2+ levels was essential for modulating stem cells fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A sustained increase in [Ca 2+ ] i with elevated Δψ m was previously reported in hematopoietic stem cells upon stress hematopoiesis to initiate cell division [ 51 ]. An increase in [Ca 2+ ] i was also found to be capable of restoring the proliferative potential and rescuing age-induced loss of MSC function [ 52 ]. The positive feedback between [Ca 2+ ] i elevation and ATP production from mitochondria can satisfy the increased energetic demand in various cell behaviors [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…A sustained increase in [Ca 2+ ] i with elevated Δψ m was previously reported in hematopoietic stem cells upon stress hematopoiesis to initiate cell division [ 51 ]. An increase in [Ca 2+ ] i was also found to be capable of restoring the proliferative potential and rescuing age-induced loss of MSC function [ 52 ]. The positive feedback between [Ca 2+ ] i elevation and ATP production from mitochondria can satisfy the increased energetic demand in various cell behaviors [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, dysregulated calcium homeostasis has been shown to function in aging-associated disorders. Previously, increased cytosolic Ca 2+ levels were observed in aging MSCs (Ahamad et al, 2021), and were correlated with age-related diseases (Madreiter-Sokolowski et al, 2020). Moreover, targeting mitochondrial calcium homeostasis is a therapeutic strategy to improve aging-associated diseases (Gao et al, 2020;Lee et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Among the various regulatory functions of mitochondria, calcium homeostasis is considered important in various pathological conditions. Dysregulated calcium status exists in aged mesenchymal stem cells and aging rat aorta (Ahamad et al, 2021;Erac et al, 2010), while we have previously shown that modulation of mitochondrial calcium overload ameliorates age-associated disorders (Gao et al, 2020). Moreover, calcium, ROS, and mitochondria comprise a close triangle that modulate not only cell function and cell fate, but also functions involved in aging and age-associated diseases (Madreiter-Sokolowski et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, we still do not know whether they support SOCE in BM-hMSCs. Nevertheless, genetic silencing of STIM1, Orai1, and/or Orai3 reduced SOCE in mouse BM-derived MSCs (BM-mMSCs) [ 79 , 80 , 81 ] and in human dental pulp-derived MSCs (DP-hMSCs) [ 82 ].…”
Section: Intracellular Ca 2+ Oscillations Regulate...mentioning
confidence: 99%